Impact of Various Plant Growth Regulators on Induction Stevia Rebaudiana Shoots in Vitro - Saleh, F. F.; Abdulkareem, A. A. (American Journal of Biology and Natural Sciences, 2025)
The study was carried out to establish and develop the protocol of micropropagation and overcome low germination rates of stevia seeds, Focusing on the role various growth regulators on induction of stevia plant shoot in vitro. The experiments involved adding different concentrations of Auxin Dichloro phenoxy aceticAcid (2.4-D) and Cytokinins Benzyle adenine (BA) and (TDZ) Thidiazuron to MS medium to determine their effect on the leaves and shoots number, shoot length and dry weight of the shoot. The results showed that interactions of 2 mg. L-1 2,4-D with 0.4 mg L-1 TDZ achieved highest average shoot length of 7.400 cm compare with the rest of the treatments. Also date appeared that the explants which grown in media containing 1mg L-1 2,4-D and 4 mg. L-1 BA achieved highest average number of leaves reaching 9.249 leaves and the number of shoots reaching 3.727 shoots compared with other treatments, which was reflected in the increase in the shoots dry weight formed, also same treatment gave an average dry weight 0.160 gm,. From this, we conclude that the multiplication and growth of the explant of the stevia was better when the MS nutrient medium was included with auxin 2,4-D and cytokinin BA.